The effect of membrane thickness on the membrane permeabilizing activity of the cyclic lipopeptide tolaasin II - Steigenberger, Jessica; Mergen, Catherine; De Roo, Vic; Geudens, Niels; Martins, José C.; Heerklotz, Heiko (Frontiers in Molecular Biosciences, 2022)
Tolaasin II is an amphiphilic, membrane-active, cyclic lipopeptide produced by Pseudomonas tolaasii and is responsible for brown blotch disease in mushroom. To better understand the mode of action and membrane selectivity of tolaasin II and related lipopeptides, its permeabilizing effect on liposomes of different membrane thickness was characterized. An equi-activity analysis served to distinguish between the effects of membrane partitioning and the intrinsic activity of the membrane-bound peptide. It was found that thicker membranes require higher local peptide concentrations to become leaky. More specifically, the mole ratio of membrane-bound peptide per lipid needed to induce 50% leakage of calcein within 1 h, Re50, increased monotonically with membrane thickness from 0.0016 for the C14:1 to 0.0070 for the C20:1 lipid-chains. Moreover, fast but limited leakage kinetics in the low-lipid regime were observed implying a mode of action based on membrane asymmetry stress in this time and concentration window. While the assembly of the peptide to oligomeric pores of defined length along the bilayer z-axis can in principle explain inhibition by increasing membrane thickness, it cannot account for the observed limited leakage. Therefore, reduced Re50 with increasing membrane thickness is attributed here to the increased mechanical strength and order of thicker membranes.